Training on Making Eco-Enzyme as a Natural Insecticide and Liquid Organic Fertilizer for Farmer Groups to Create Environmentally Friendly Agriculture - Abdul Hadjranul Fatah; I Nyoman Sudyana; Abudarin Abudarin; Soaloon Sinaga; Wahyu Supriyati; Retno Agnestisia; Dessy Analinta; Sugeng Mashabhi (Universitas Lambung Mangkurat, 2024)
Habaring Urung is a sub-district where most farmers work and is one of the local vegetable and fruit-producing areas in Palangka Raya City. So far, farmers tend to use synthetic insecticides and chemical fertilisers obtained from agricultural shops to cultivate plants. Apart from expensive operational costs, synthetic insecticides and chemical fertilisers are known to damage the environment if used over a long period. Therefore, this program aimed to equip the knowledge and skills of farmer groups in the Habaring Hurung Sub-district to make environmentally friendly insecticides and liquid organic fertilisers. This activity was carried out using the Participatory Action Research (PAR) method. Implementation of activities consisted of several stages, i.e., preparation, problem identification, focus group discussions to determine programs that suit the problem, program implementation through training, and evaluation by administering questionnaires. This program was implemented in September 2023 at the Habaring Hurung Sub-district Office Hall with 39 activity participants. The enthusiasm and active participation of participants during the implementation of the program showed a positive response. The questionnaire results as part of the program evaluation also showed that almost all participants agreed (72.22%) and strongly agreed (27.78%) that participants' knowledge and skills increased after participating in this activity program. In addition, this program is also considered very useful and is planned to be continued independently by the activity participants. It shows that the program has increased the knowledge and skills of farmer groups in the Habaring Hurung Sub-district in making insecticides and liquid organic fertilisers that are environmentally friendly and of high value to support sustainable agricultural policies.